Makna Tinder sebagai Tempat Mendapatkan Teman Hidup - Annisarizki Annisarizki (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2018)
Tinder is one of the online dating search applications are busy used. Tinder provides a change in the way society finds friends, the process of getting a life partner begins with face-to-face introductions, passing approach stages with partners, exploring stages to get to know each other, then being intimate with dates. But when Tinder takes the time it takes not long to decide to marry someone new in their life, this is what makes the researcher interested to know how the phenomenon of searching a friend live through online dating application about the meaning of Tinder as a place to get a life partner. The theory used in this research is Computer Mediated Communication (CMC) theory and Social Penetration theory. This research also uses phenomenology method with qualitative approach. The results showed that the informants used Tinder because of the invitation from friends. They have limited time and environment, so they become social media (Tinder) as a solution to get the soul mate.But they still select the match couples in Tinder according to the criteria they are in the real world, for they get married.